Comparative efficacy of commercial infectious bursal disease vaccination strategies against emerging novel variant IBDV (Genotype A2d) - Kamal Samy Ahmed Mohamed Issa; Hany Fawzy Ellakany; Ahmed Ramadan Gado; Shady Hesham Elrayes; Ismail Ismail Abughanima; Ahmed R. Elbestawy; Rania F. El Naggar; Ahmed H. Salaheldin; Mohammed A. Abdelsabour; Hatem S. Abd El-Hamid; Mohammed A. Rohaim (Comparative Immunology, Microbiology and Infectious Diseases, 2026)

Metabolomic approach to explore the chemical composition and health benefits of macroalgae: A comprehensive study of Palmaria palmata, Ascophyllum nodosum, and Chondrus crispus - Natália Čmiková; Milena D. Vukić; Nenad L. Vukovic; Jaroslav Havlík; Hanán Issa-Issa; Ángel A. Carbonell-Barrachina; Ivona Jančo; Vittorio Vinciguerra; Stefania Garzoli; Miroslava Kačániová (Food Chemistry, 2025)

Is mechanized conservation agriculture a promising solution for smallholder farmers? Evaluating its short-term agronomic and economic performance in Ethiopia - Bisrat G. Awoke; Thomas Daum; Karlheinz Köller; Dereje A. Anawte; Mubarek M. Issa; Teshome B. Gutema; Debele D. Enki; Godfrey Omulo; Regina Birner (Field Crops Research, 2025)

End-to-end deep SAE-DNN model for predicting Egyptian buffalo calf sex, weight, and daily milk yield - Sali Issa; Montaser Elsayed Ali; Qi Wang; Fatimah A. Al-Saeed; Mohamed Abdelrahman (Tropical Animal Health and Production, 2025)

KI-gestütztes Videomonitoring aquatischer Ökosysteme - Chancen, Grenzen und Praxisanforderungen - Jeffrey A. Tuhtan; Bernd Mockenhaupt; Frederic de Schaetzen; Rodrigo W. Issa; Adrien Bertaud; Damien Sidler; Henning Müller; Christian Haas (WASSERWIRTSCHAFT, 2025)

Development of Bacillus spp for controlling wilt disease and improving the growth of tomato - Najeeb M. Almasoudi; Nashwa M. A. Sallam; Esmat F. Ali; Abeer S. Alqurashi; Ahmed A. Issa; Fayez Althobaiti; Mohamed Housny; Hanan AlOmari; Kamal A. M. Abo-Elyousr (European Journal of Plant Pathology, 2025)

Managing anthracnose fruit rot disease in pepper caused by Colletotrichum capsici via potash alum and frankincense essential oil - Mansour M. El-Fawy; Muhammad Imran; Esmat F. Ali; Abeer S. Alqurashi; Ahmed A. Issa; Rabee A. Emam; Mohamed F. Abd El-Mageed; Najeeb M. Almasoudi; Nashwa M. A. Sallam; Kamal A. M. Abo-Elyousr (Journal of Plant Pathology, 2025)

Biosynthesis of trimetallic nanoparticles and their biological applications: a recent review - Amr H. Hashem; Ebrahim Saied; Bahaa M. Badr; Mohamed Soliman Dora; Mahmoud A. Diab; Amer Morsy Abdelaziz; Fathy M. Elkady; Mohamed Abdelrahman Ali; Nasser Ibrahim Issa; Ziad A. Hamdy; Mohamed E. Nafea; Ahmed Nageh Khalifa; et al. (Archives of Microbiology, 2025)

Design of New Wet Heterogeneous Photo Oxidation Process for Refinery Waste Water Treatment in Photo Baffled Reactor - Yousif. S. Issa; Qahtan A. Mahmood; Jasim I. Humadi; Ghanim Hassan; Rajesh Haldhar (Water, Air, & Soil Pollution, 2025)

Effectiveness of biochar and wood vinegar from guava trees in controlling Fusarium verticillioides and enhancing growth and anatomical traits of maize (Zea mays L.) - Mansour M. El-Fawy; Ayman S. Saeed; Mohamed K. Abou-Shlell; Mahmoud A. Soliman; Esmat F. Ali; Ahmed A. Issa; Kamal A. M. Abo-Elyousr; Muhammad Imran; Asmaa S. El-Nagar (Journal of Plant Diseases and Protection, 2024)

Epigallocatechin gallate-rich fraction alleviates histamine-induced neurotoxicity in rats via inactivating caspase-3/JNK signaling pathways - Eman I. Hassanen; Hayam A. Mansour; Marwa Y. Issa; Marwa A. Ibrahim; Wafaa A. Mohamed; Mahmoud A. Mahmoud (Food and Chemical Toxicology, 2024)

First report of rust disease caused by Puccinia Porri on Egyptian leek in Egypt and its control by bergamot essential oil - Kamal A. M. Abo-Elyousr; Najeeb M. Almasoudi; Mansour M. El-Fawy; Ayman S. Saeed; Sameh H. E. Hamada; Esmat F. Ali; Ahmed A. Issa; Fayez Althobaiti; Ehab E. E. Korrat (Journal of Plant Pathology, 2024)

Clinical and Molecular Profiles of a Cohort of Egyptian Patients with Collagen VI-Related Dystrophy - Wessam E. Sharaf-Eldin; Karima Rafat; Mahmoud Y. Issa; Hasnaa M. Elbendary; Noura R. Eissa; Bahaa Hawaary; Nagwa E. A. Gaboon; Reza Maroofian; Joseph G. Gleeson; Mona L. Essawi; Maha S. Zaki (Journal of Molecular Neuroscience, 2024)
Collagen VI-related dystrophies (COL6-RD) display a wide spectrum of disease severity and genetic variability ranging from mild Bethlem myopathy (BM) to severe Ullrich congenital muscular dystrophy (UCMD) and the intermediate severities in between with dual modes of inheritance, dominant and recessive. In the current study, next-generation sequencing demonstrated potential variants in the genes coding for the three alpha chains of collagen VI ( COL6A1 , COL6A2 , or COL6A3 ) in a cohort of Egyptian patients with progressive muscle weakness ( n = 23). Based on the age of disease onset and the patient clinical course, subjects were diagnosed as follows: 12 with UCMD, 8 with BM, and 3 with intermediate disease form. Fourteen pathogenic variants, including 5 novel alterations, were reported in the enrolled subjects. They included 3 missense, 3 frameshift, and 6 splicing variants in 4, 3, and 6 families, respectively. In addition, a nonsense variant in a single family and an inframe variant in 3 different families were also detected. Recessive and dominant modes of inheritance were recorded in 9 and 8 families, respectively. According to ACMG guidelines, variants were classified as pathogenic ( n = 7), likely pathogenic ( n = 4), or VUS ( n = 3) with significant pathogenic potential. To our knowledge, the study provided the first report of the clinical and genetic findings of a cohort of Egyptian patients with collagen VI deficiency. Inter- and intra-familial clinical variability was evident among the study cohort.

Biodegradation of petroleum hydrocarbons using a novel bacterial strain isolated from hydrocarbons contaminated soil of Saudi Arabia - Mohammad Hazaimeh; Belal Muneeb Kanaan; Faleh A. AlFaleh; Mahmoud M. Elhaig; Emran Issa Khamaiseh; Qamar Zia; Mohammed Alaidarous; Chandra Shekhar Seth; Noorah Alsowayeh; Faheem Ahmad (Biocatalysis and Agricultural Biotechnology, 2024)

Synthesis of adamantane-monoterpene conjugates with 1,3,4-thiadiazol-2(3H)-imine linker and evaluation of their inhibitory activity against TDP1 - Aldar A. Munkuev; Alexandra L. Zakharenko; Tatyana E. Kornienko; Nadezhda S. Dyrkheeva; Ekaterina S. Ilina; Evgeniy V. Suslov; Fatima Issa; Chigozie Achara; Jóhannes Reynisson; Konstantin P. Volcho; Nariman F. Salakhutdinov; Olga I. Lavrik (Medicinal Chemistry Research, 2024)

Quality assessment of Vitellaria paradoxa seed oil obtained under different extraction conditions and solvents - Ibanga O. Isaac; Iniobong S. Enengedi; Issa A. Abdulazeez (Sustainable Chemistry and Pharmacy, 2023)

Full-scale testing and nonlinear finite element analysis of a pioneering fully prefabricated noise barrier wall system - Ahmad G. Elrefae; Mohsen A. Issa (Engineering Structures, 2023)

The association of in-utero exposure to polycyclic aromatic hydrocarbons and umbilical liver enzymes - Li Wanying; Mariami T. Okromelidze; Andrés Alexis Ramírez-Coronel; Angelina O. Zekiy; Rasha Fadhel Obaid; Zanko Hassan Jawhar; Gamal A. Gabr; Mais Mazin Al-Hamdani; Sokaina Issa Kadhim; Yasser Fakri Mustafa; Moslem Lari Najafi; Mohammad Miri (Science of The Total Environment, 2023)

Biosynthesis of zinc oxide nanoparticles using the supernatant of Weissella cibaria UPM22MT06 and its antibacterial and cytotoxicity properties - Ahmed Issa Al-Tameemi; Mas Jaffri Masarudin; Raha Abdul Rahim; Toby Mills; Verlaine J Timms; Brett A Neilan; Nurulfiza Mat Isa (Biologia, 2023)

High multidrug resistance of Listeria monocytogenes and association with water sources in sheep and goat dairy flocks in Jordan - Mohammad M. Obaidat; Issa A. AlShehabat (Preventive Veterinary Medicine, 2023)

A review study summarizes the main characterization techniques of nano-composite photocatalysts and their applications in photodegradation of organic pollutants - Zaid H. Jabbar; Bassim H. Graimed; Ayah A. Okab; Mohammed Abdullah Issa; Saad H. Ammar; Hussein J. Khadim; Yasmeen A. Shafiq (Environmental Nanotechnology, Monitoring & Management, 2023)

Optimal parameters extracting of fuel cell based on Gorilla Troops Optimizer - Mohamed Abd Elaziz; Laith Abualigah; Mohamed Issa; Ahmed A. Abd El-Latif (Fuel, 2023)

Exploratory Study on Lercanidipine Hydrochloride Polymorphism: pH-Dependent Solubility Behavior and Simulation of its Impact on Pharmacokinetics - Ilia Alekseevich Repin; Raimar Loebenberg; John DiBella; António C. L. Conceição; Manuel E. Minas da Piedade; Humberto G. Ferraz; Michele G. Issa; Nadia A. Bou-Chacra; Catharine F. M. Ermida; Gabriel L. B. de Araujo (AAPS PharmSciTech, 2021)

The pervasive and multifaceted influence of biocrusts on water in the world's drylands - David J. Eldridge; Sasha Reed; Samantha K. Travers; Matthew A. Bowker; Fernando T. Maestre; Jingyi Ding; Caroline Havrilla; Emilio Rodriguez‐Caballero; Nichole Barger; Bettina Weber; Anita Antoninka; Jayne Belnap; et al. (Global Change Biology, 2020)
The capture and use of water are critically important in drylands, which collectively constitute Earth's largest biome. Drylands will likely experience lower and more unreliable rainfall as climatic conditions change over the next century. Dryland soils support a rich community of microphytic organisms (biocrusts), which are critically important because they regulate the delivery and retention of water. Yet despite their hydrological significance, a global synthesis of their effects on hydrology is lacking. We synthesized 2,997 observations from 109 publications to explore how biocrusts affected five hydrological processes (times to ponding and runoff, early [sorptivity] and final [infiltration] stages of water flow into soil, and the rate or volume of runoff) and two hydrological outcomes (moisture storage, sediment production). We found that increasing biocrust cover reduced the time for water to pond on the surface (−40%) and commence runoff (−33%), and reduced infiltration (−34%) and sediment production (−68%). Greater biocrust cover had no significant effect on sorptivity or runoff rate/amount, but increased moisture storage (+14%). Infiltration declined most (−56%) at fine scales, and moisture storage was greatest (+36%) at large scales. Effects of biocrust type (cyanobacteria, lichen, moss, mixed), soil texture (sand, loam, clay), and climatic zone (arid, semiarid, dry subhumid) were nuanced. Our synthesis provides novel insights into the magnitude, processes, and contexts of biocrust effects in drylands. This information is critical to improve our capacity to manage dwindling dryland water supplies as Earth becomes hotter and drier.

Anticoccidial effects of Khaya senegalensis aqueous stem bark extract on broiler chickens experimentally infected with Eimeria species - Issa A. Muraina; Jurbe G. Gotep; James T. Tanko; ThankGod E. Onyiche; Oladimeji B. Aladelokun; Christiana C. Dapuliga; Gilead E. Forcados; Nonyelim Ozele; Ann L. Samuel; Olusola O. Oladipo; Olatunde B. Akanbi; Philip A. Okewole; et al. (Tropical Animal Health and Production, 2020)

Myocardial adaptability in young and older-aged sea-level habitants sojourning at Mt Kilimanjaro: are cardiac compensatory limits reached in older trekkers? - Glenn M. Stewart; Courtney M. Wheatley-Guy; Norman R. Morris; Kirsten E. Coffman; Jan Stepanek; Alex R. Carlson; Amine Issa; Michael A. Schmidt; Bruce D. Johnson (European Journal of Applied Physiology, 2020)

Crystal structure and configuration revision of 9-hydroxy-7,8-dehydro-sarcotrocheliol and sarcotrocheliol - Abdelaaty Hamed; Marwa Y. Issa; Mohamed A. Ghani; Marcel Frese; Beate Neumann; Hans Georg Stammler; Norbert Sewald; Mohamed Shaaban (Natural Product Research, 2019)

Biological control of damping-off of tomato caused by Pythium aphanidermatum by using native antagonistic rhizobacteria isolated from Omani soil - Hanan S. Al-Hussini; Amna Y. Al-Rawahi; Abdullah A. Al-Marhoon; Shurooq A. Al-Abri; Issa H. Al-Mahmooli; Abdullah M. Al-Sadi; Rethinasamy Velazhahan (Journal of Plant Pathology, 2019)

New pyranosyl cembranoid diterpenes from Sarcophyton trocheliophorum - Mohamed Shaaban; Marwa Y. Issa; Mohamed A. Ghani; Abdelaaty Hamed; Ahmed B. Abdelwahab (Natural Product Research, 2019)

Comparison of bonobo and chimpanzee brain microstructure reveals differences in socio-emotional circuits - Habon A. Issa; Nicky Staes; Sophia Diggs-Galligan; Cheryl D. Stimpson; Annette Gendron-Fitzpatrick; Jared P. Taglialatela; Patrick R. Hof; William D. Hopkins; Chet C. Sherwood (Brain Structure and Function, 2019)

Effect of recycled glass powder on properties of cementitious materials contains styrene butadiene rubber - Asmahan Issa Jubeh; Doha M. Al Saffar; Bassam A. Tayeh (Arabian Journal of Geosciences, 2019)

Naringenin mitigates titanium dioxide (TiO2)-induced chronic arthritis in mice: role of oxidative stress, cytokines, and NFκB - Marília F. Manchope; Nayara A. Artero; Victor Fattori; Sandra S. Mizokami; Dimitrius L. Pitol; João P. M. Issa; Sandra Y. Fukada; Thiago M. Cunha; José C. Alves-Filho; Fernando Q. Cunha; Rubia Casagrande; Waldiceu A. Verri (Inflammation Research, 2018)

Contributing Causes of Injury or Death in Grain Entrapment, Engulfment, and Extrication - Salah Fuad Issa; William E. Field; Charles V. Schwab; Fadi S. Issa; Eric A. Nauman (Journal of Agromedicine, 2017)

A novel frameshift mutation in the sterol 27-hydroxylase gene in an Egyptian family with cerebrotendinous xanthomatosis without cataract - Mohamed S. Abdel-Hamid; Mahmoud Y. Issa; Ghada A. Otaify; Maha S. Zaki (Metabolic Brain Disease, 2017)

In Vitro Comparative Evaluation of Antioxidant Activity of Hydrophobic and Hydrophilic Extracts from Algicolous Fungi - Awatief F. Hifney; Mustafa A. Fawzy; Khayria M. Abdel-Gawad; Ahmed A. Issa; Mohamed Gomaa (Journal of Aquatic Food Product Technology, 2017)

Variation of hydrogeochemical characteristics of water in surface flows, shallow wells, and boreholes in the coastal city of Douala (Cameroon) - Wilson Y. Fantong; Brice T. Kamtchueng; Beatrice Ketchemen-Tandia; Doris Kuitcha; Josephine Ndjama; Alain T. Fouepe; Gloria E. Takem; Issa; Mengnjo J. Wirmvem; Serges L. Bopda Djomou; Andrew A. Ako; George E. Nkeng; et al. (Hydrological Sciences Journal, 2016)

Thermal maturity and hydrocarbon generation of the Dawi Formation, Belayim Marine Oil Field, Gulf Of Suez, Egypt: a 1D Basin Modeling Case Study - Mohamed Moustafa Afife; Mohamed Abu Al-Atta; Mohammed A. Ahmed; Ghalib Ibrahim Issa (Arabian Journal of Geosciences, 2016)

Biodegradation of Palisada perforata (Rhodophyceae) and Sargassum sp. (Phaeophyceae) biomass by crude enzyme preparations from algicolous fungi - Mohamed Gomaa; Awatief F. Hifney; Mustafa A. Fawzy; Ahmed A. Issa; Khayria M. Abdel-Gawad (Journal of Applied Phycology, 2015)

Spatio-temporal, environmental factors, and host identity shape culturable-epibiotic fungi of seaweeds in the Red Sea, Egypt - Khayria M. Abdel-Gawad; Awatief F. Hifney; Ahmed A. Issa; Mohamed Gomaa (Hydrobiologia, 2014)

Quantifying the response of free-ranging mammalian herbivores to the interplay between plant defense and nutrient concentrations - Miguel A. Bedoya-Pérez; Daniel D. Issa; Peter B. Banks; Clare McArthur (Oecologia, 2014)

Analysing the relationship between land units and plant communities: The case of Socotra Island (Yemen) - F. Attorre; A. Issa; L. Malatesta; A. Adeeb; M. De Sanctis; M. Vitale; A. Farcomeni (Plant Biosystems, 2014)

Susceptibility gene search for nephropathy and related traits in Mexican–Americans - Farook Thameem; Issa A. Kawalit; Sharon G. Adler; Hanna E. Abboud (Molecular Biology Reports, 2013)

Modulation of cytochrome P450 1 (Cyp1) by vanadium in hepatic tissue and isolated hepatocyte of C57BL/6 mice - Ghada Abdelhamid; Issa E. A. Amara; Anwar Anwar-Mohamed; Ayman O. S. El-Kadi (Archives of Toxicology, 2013)

Differential modulation of aryl hydrocarbon receptor regulated enzymes by arsenite in the kidney, lung, and heart of C57BL/6 mice - Anwar Anwar-Mohamed; Ghada Abdelhamid; Issa E. A. Amara; Ayman O. S. El-Kadi (Archives of Toxicology, 2012)

Multiple source imagery and linear features for detection of urban expansion in Aqaba City, Jordan - Rami Issa Al-Ruzouq; Abdallah Al-Zoubi; Emad E. Akawi; Abdalrahman A. Abueladas; Tina M. Niemi (International Journal of Remote Sensing, 2012)

Synthesis of new series of pyrazolo[4,3-d]pyrimidin-7-ones and pyrido[2,3-d]pyrimidin-4-ones for their bacterial and cyclin-dependent kinases (CDKs) inhibitory activities - Detlef Geffken; Raafat Soliman; Farid S. G. Soliman; Magdi M. Abdel-Khalek; Doaa A. E. Issa (Medicinal Chemistry Research, 2011)

Rate of seawater intrusion estimated by geophysical methods in an arid area: Al Khabourah, Oman - Osman A. E. Abdalla; Mubarik Ali; Khalifa Al-Higgi; Hilal Al-Zidi; Issa El-Hussain; Said Al-Hinai (Hydrogeology Journal, 2010)

Parasite Prevalence, Abundance, and Diversity in a Semi-free-ranging Colony of Mandrillus sphinx - Joanna M. Setchell; Issa-Ben Bedjabaga; Benoit Goossens; Patricia Reed; E. Jean Wickings; Leslie A. Knapp (International Journal of Primatology, 2007)

Making a friend from a foe: expressing a GroEL gene from the whitefly Bemisia tabaci in the phloem of tomato plants confers resistance to tomato yellow leaf curl virus - F. Akad; A. Eybishtz; D. Edelbaum; R. Gorovits; O. Dar-Issa; N. Iraki; H. Czosnek (Archives of Virology, 2007)

Secondary sexual characters and female quality in primates - Joanna M. Setchell; Marie J. E. Charpentier; Issa-Ben Bedjabaga; Patricia Reed; E. Jean Wickings; Leslie A. Knapp (Behavioral Ecology and Sociobiology, 2006)

Parasitic Nematodes in the Chimpanzee Population on Rubondo Island, Tanzania - Klara J. Petrzelkova; Hideo Hasegawa; Liza R. Moscovice; Taranjit Kaur; Mwanahamissi Issa; Michael A. Huffman (International Journal of Primatology, 2006)

Artificial Insemination Using Local Cattle Breeds in Niger - F. Cristofori; M. Issa; A. Yenikoye; G. Trucchi; G. Quaranta; M. Chanono; C. Semita; H. Marichatou; M. Mattoni (Tropical Animal Health and Production, 2005)

A methodological study on participatory barley breeding II. Response to selection - S. Ceccarelli; S. Grando; M. Singh; M. Michael; A. Shikho; M. Al Issa; A. Al Saleh; G. Kaleonjy; S.M. Al Ghanem; A.L. Al Hasan; H. Dalla; S. Basha; et al. (Euphytica, 2003)

Proline alleviates heavy metal stress inScenedesmus armatus - A. E. El-Enany; A. A. Issa (Folia Microbiologica, 2001)

Effect of manganese and calcium deficiency on the growth and oxygen exchange ofScenedesmus intermedius cultured for successive generations - M. S. Adam; A. A. Issa (Folia Microbiologica, 2000)

Influence of selenium on toxicity of some heavy metals in the green algaScenedesmus obliquus - A. A. Issa; M. S. Adam (Folia Microbiologica, 1999)

Molecular mechanism of vitamin D receptor action - L. L. Issa; G. M. Leong; J. A. Eisman (Inflammation Research, 1998)

Effect of Ca2+ on the detoxification of Cd2+ byScenedesmus obliquus cells at low or high temperature - A. A. Issa; M. S. Adam; R. Abdel-Basset (Folia Microbiologica, 1998)